Immune response effects of a swimming session remain for more than 24 hours - Morgado, J.; Monteiro, C. P.; Matias, C.; Alves, F.; Seixas, M. T.; Alvim, M.; Bourbon, M.; Laires, M. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction The effect of exercise over the immune response along the recovery period has revealed inconsistent findings especially in swimming training. The purpose of this study was to evaluate the immune systemic response to a high intensity swim training session during a 24h recovery period. Methods: A group of 36 Portuguese male swimmers (16 ± 0.4 yrs; 186 ± 12 cm; 65 ± 1.3 Kg) performed a selected swim training session with a high intensity main set at the end of the first macrocycle of the season. Blood samples were collected before (Pre), immediately after (Post), 2 h after (Post2h) and 24 h after (Post24h) the swimming session, by standard procedures for assessment of Haemogram and Leukogram (automated counter Beckman Coulter LH 750) and Lymphocytes subpopulations (FACS Calibur Becton, Dickinson and Company) including CD3+, CD4+, CD8+, CD16+ and CD19+. ANOVA for repeated measures with Bonferroni post-hoc test or Friedman test with pairwise comparisons were used for the assessment of exercise effects. Statistical significance was considered at p < 0.05. Results: At Post, significantly lower values of haemoglobin, monocytes, eosinophils, total lymphocytes and all the subpopulations evaluated were observed. Platelets, neutrophils and CD4+/CD8+ ratio were elevated at Post but leukocytes did not change significantly. At Post2h, monocytes and platelets had return to Pre values; haemoglobin, eosinophils, continued to decrease; total lymphocytes, CD3+, CD4+, CD8+ and CD16+ maintained lower values; CD19+ increased significantly regarding Post but remained below Pre; neutrophils continued to rise, CD4+/CD8+ ratio maintained higher values and leukocytes increased. At Post24h, neutrophils, eosinophils, CD8+, CD16+ and CD4+/CD8+ ratio recovered to Pre levels; total lymphocytes, CD3+ and CD4+ augmented comparing to Pos2h but stayed above Pre; CD19+ remained lower than Pre while leukocytes and monocytes decreased to values below Pre. Discussion: A demanding swimming session seems to provoke a significant acute depression of the Imune System suggesting that a 24h period is insufficient to attain total recovery. These findings support the idea that exercise induces immune suppression and increases susceptibility to infections after high intensity training sessions.